Diagnostic value of shear wave ultrasound elastography of tibial nerve in patients with diabetic peripheral neuropathy - Heba R. Ibrahim (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Diabetic peripheral neuropathy (DPN) is a major complication of Diabetes mellitus. So this study aimed at investigation of the value of tibial nerve stiffness measured by shear wave ultrasound elastography (SWE) for detection of DPN. This case–control study involved 50 patients with DPN, 50 patients with diabetes mellitus but without DPN, and 50 healthy controls. Clinical examination, nerve conduction study of both tibial nerves, high resolution ultrasound and SWE to assess cross sectional area "CSA" of tibial nerves, and tibial nerves mean stiffness, respectively. ROC curve analysis was also performed. Results Mean tibial nerve stiffness by SWE was higher in patients with DPN compared to other groups (P value < 0.001). The CSA of the tibial nerve in the DPN group was significantly larger than that in the other groups (P value = 0.01). The cutoff value by ROC curve analysis for tibial nerve stiffness to differentiate patients with DPN and control group was 70.6 kPa (P value < 0.001, 95.4% sensitivity, 94.7% specificity, AUC = 0.963), while 86.5 kPa was the optimal cutoff point to differentiate patients with DPN and other groups with a 94.6% sensitivity, 93.8% specificity, AUC of 0.975 and P value < 0.001. Higher diagnostic accuracy was found when combination of SWE and high resolution US (high resolution US + shear wave; 0.987, P value < 0.001). Conclusions Tibial nerve stiffness was increased in patients with DPN. SWE can be used as an effective complementary method in diagnosis of DPN with high sensitivity and accuracy.